2017
DOI: 10.1002/2016ms000885
|View full text |Cite
|
Sign up to set email alerts
|

Significant impacts of irrigation water sources and methods on modeling irrigation effects in the ACMELand Model

Abstract: An irrigation module considering irrigation water source and irrigation method has been incorporated into the ACME Land Model (ALM). Global numerical experiments were conducted to investigate irrigation effects and their sensitivity to irrigation water sources and irrigation methods. All simulations shared the same irrigation soil moisture target constrained by a global census data set of irrigation amounts. Irrigation has large impacts on terrestrial water balances especially in regions with extensive irrigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
107
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 72 publications
(107 reference statements)
1
107
0
Order By: Relevance
“…Levis et al 2012, Liu et al 2016, of human water-management modeling (e.g. Voisin et al 2017), and of irrigation methods (Leng et al 2017) in ESMs will accelerate the inclusion of more realistic irrigation-crop-water resource models and improve the representation of their interactions with weather and climate.…”
Section: Discussionmentioning
confidence: 99%
“…Levis et al 2012, Liu et al 2016, of human water-management modeling (e.g. Voisin et al 2017), and of irrigation methods (Leng et al 2017) in ESMs will accelerate the inclusion of more realistic irrigation-crop-water resource models and improve the representation of their interactions with weather and climate.…”
Section: Discussionmentioning
confidence: 99%
“…To show the decrease in terrestrial water storage over the study area, which is related to the groundwaterfed irrigation, we used the Gravity Recovery and Climate Experiment Tellus monthly land water mass grids NetCDF release 5.0 [27] to analyze the seasonal land water storage change over the NCP (31…”
Section: Methodsmentioning
confidence: 99%
“…drip, sprinkler, and flood irrigation) and water source (i.e. surface water and groundwater) may have an effect on simulated results, however Leng et al [31] found that it can only affect the runoff and water table depth, and have no effect on evapotranspiration. Therefore, this study did not consider the different irrigation methods and water source.…”
mentioning
confidence: 99%
“…To address this limitation, Leng et al (2014Leng et al ( , 2015 introduced a source water accounting scheme to CLM that withdraws water for irrigation in response to simulated irrigation applications. Like other efforts (Leng et al, 2017;Li et al, 2016;Mahalov et al, 2016;Ozdogan et al, 2010), irrigation applications in this formulation are demand-driven, and source water is withdrawn to meet the application required by the irrigation module. Because the model development was performed in CLM rather than a simplified GHM, Leng et al (2014Leng et al ( , 2015 were able to investigate local hydrological feedbacks influencing irrigation efficiency.…”
Section: Introductionmentioning
confidence: 99%